Relative performance of customized and universal probe sets in target enrichment: A case study in subtribe Malinae. (23rd July 2021) - Ufimov, Roman; Zeisek, Vojtěch; Píšová, Soňa; Baker, William J.; Fér, Tomáš; van Loo, Marcela; Dobeš, Christoph; Schmickl, Roswitha
Abstract : Premise: Custom probe design for target enrichment in phylogenetics is tedious and often hinders broader phylogenetic synthesis. The universal angiosperm probe set Angiosperms353 may be the solution. Here, we test the relative performance of Angiosperms353 on the Rosaceae subtribe Malinae in comparison with custom probes that we specifically designed for this clade. We then address the impact of bioinformatically altering the performance of Angiosperms353 by replacing the original probe sequences with orthologs extracted from the Malus domestica genome. Methods: To evaluate the relative performance of these probe sets, we compared the enrichment efficiency, locus recovery, alignment length, proportion of parsimony‐informative sites, proportion of potential paralogs, the topology and support of the resulting species trees, and the gene tree discordance. Results: Locus recovery was highest for our custom Malinae probe set, and replacing the original Angiosperms353 sequences with a Malus representative improved the locus recovery relative to Angiosperms353. The proportion of parsimony‐informative sites was similar between all probe sets, while the gene tree discordance was lower in the case of the custom probes. Discussion: A custom probe set benefits from data completeness and can be tailored toward the specificities of the project of choice; however, Angiosperms353 was equally as phylogenetically informative as the custom probes. We therefore recommend using both a custom probe set and Angiosperms353 to facilitate large‐scale systematic studies, where financially possible.